Successful Treatment of High-Level Aminoglycoside-Resistant Enterococcus faecalis Bacteremia in a Preterm Infant with Ampicillin and Cefotaxime - Jennifer Tam; Santina J. Lee; Vibhuti Shah; Shaun K. Morris (Case Reports in Infectious Diseases)
Enterococcal bloodstream infections are usually treated with single-agent antibiotics. In persistent infections, synergistic combination therapy is often required with a beta-lactam and an aminoglycoside antibiotic. High-level aminoglycoside-resistant (HLAR) enterococci are increasingly prevalent and preclude the use of this combination. The use of ampicillin with a third-generation cephalosporin to treat endovascular HLAR Enterococcus infections is becoming more established in the adult population; however, the literature on treatment of such infections in children remains scarce. We report a preterm neonate with persistent HLAR Enterococcus faecalis bacteremia from day of life 9 to 17 despite treatment with ampicillin and vancomycin. On day of life 17, antibiotic treatment was switched to ampicillin and cefotaxime, with subsequent clearance of blood cultures on day of life 20. To our knowledge, this is the first report illustrating the use of ampicillin and cefotaxime for an HLAR E. faecalis infection in a neonate.